A T Cell Suppressive Circuitry Mediated by CD39 and Regulated by ShcC/Rai Is Induced in Astrocytes by Encephalitogenic T Cells - Ulivieri, Cristina; De Tommaso, Domiziana; Finetti, Francesca; Ortensi, Barbara; Pelicci, Giuliana; D'Elios, Mario Milco; Ballerini, Clara; Baldari, Cosima T. (Frontiers in Immunology, 2019)
Multiple sclerosis is an autoimmune disease caused by autoreactive immune cell infiltration into the central nervous system leading to inflammation, demyelination and neuronal loss. While myelin-reactive Th1 and Th17 are centrally implicated in multiple sclerosis pathogenesis, the local CNS microenvironment, which is shaped by both infiltrated immune cells and central nervous system resident cells, has emerged a key player in disease onset and progression. We have recently demonstrated that ShcC/Rai is as a novel astrocytic adaptor whose loss in mice protects from experimental autoimmune encephalomyelitis. Here, we have explored the mechanisms that underlie the ability of Rai-/- astrocytes to antagonize T cell-dependent neuroinflammation. We show that Rai deficiency enhances the ability of astrocytes to upregulate the expression and activity of the ectonucleotidase CD39, which catalyzes the conversion of extracellular ATP to the immunosuppressive metabolite adenosine, through both contact-dependent and -independent mechanisms. As a result, Rai-deficient astrocytes acquire an enhanced ability to suppress T-cell proliferation, which involves suppression of T cell receptor signaling and upregulation of the inhibitory receptor CTLA-4. Additionally, Rai-deficient astrocytes preferentially polarize to the neuroprotective A2 phenotype. These results identify a new mechanism, to which Rai contributes to a major extent, by which astrocytes modulate the pathogenic potential of autoreactive T cells.